General Characteristics of Guarantees of Journalists Rights in Ukraine - KOMISAROV, Oleksandr H.; CHYSTOKLETOV, Leontii G.; OSTAPENKO, Oleksii I.; SHUSTROVA, Kseniya V.; KHYTRA, Oleksandra L.; SHYSHKO, Valerii V. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019DO - 10.14505//jarle.v10.1(39).25, 2019)
The relevance of the article is that guarantees for the journalists' rights realization became one of the priority directions of legislation improvement not only in Ukraine, but all over the world because It is precisely this career that involves risks in the course of professional activities associated with the location of media workers in the areas of hostilities and emergencies. The article is devoted to the general characteristics of guarantees of the journalists’ rights in Ukraine. The leading method for the study of this problem is the method of analysis, which made it possible to study the existing legislative framework on the subject and identify short comings concerning the rights of journalists. The proposal of defining the term ‘journalist’ in the legislation of Ukraine is substantiated and the guarantees of journalists' rights are determined. The classification of guarantees of the rights of journalists is given based on the analysis of the current legislation. It is made the conclusion on the necessity of passing the law On Protection of Professional Activities of Journalists in Ukraine.